ASSESSMENT OF MICROBIOLOGICAL LOAD OF SMALL RUMINANT CARCASSES, LIVERS, SOME LYMPH NODES, TOOLS AND KNIFE SAMPLES IN SLAUGHTERHOUSE - Durmusoglu, Halil; Incili, Gokhan Kursad; Gungoren, Alper; Ilhak, Osman Irfan (Univ Ljubljana, 2020)
The aim of this study was to determine the microbiological loads of small animal carcasses, carcass lymph nodes, whole liver surface, liver lymph nodes and some tools contacting with carcass and offal. Total 630 samples taken from small animal carcasses, livers, hepatic lymph nodes, subiliac and prescapular lymph nodes, staff knives and slaughterhouse tools samples (stainless steel table, plastic crates, offal carts) were investigated for mesophilic aerobic bacteria, Enterobacteriaceae, Escherichia coil counts and Salmonella spp. The mean total aerobic mesophilic bacteria (TAMB), Enterobacteriaceae and E. coil numbers of the carcasses were 3.6, 0.6, and 0.1 log(10) CFU/cm(2), respectively, and the most contaminated region among the carcass sampling points was flank. The mean TAMB, Enterobacteriaceae and E. coli counts of the liver surfaces were 6.0, 3.7, 2.9 log(10) CFU/liver, respectively. The average TAMB, Enterobacteriaceae and E. coil numbers of the knives were found as 6.3, 2.9 and 2.1 log(10) CFU/blade, and the average TAMB,Enterobacteriaceae and E. coli counts of the slaughterhouse surfaces were 5.1, 1.6, 0.5 log(10) CFU/cm(2). Salmonella spp. was detected in 4% of the liver samples and 10% of the knives samples. Consequently, the presence of Salmonella on the surface of livers and blades, and high number of E. coli on the livers, blades and tools show that a public health risk may arise at any time, and staff should pay extra attention to the Good Hygiene Practices and Food Safety Management Systems (such as HACCP) applied in slaughterhouses.
Ocena mikrobioloŠke obremenitve trupov malih pre?vekovalcev, jeter in nekaterih bezgavk ter orodij in no?ev v klavnici
Keywords: carcass; liver; lymph node; microbiological quality; Enterobacteriaceae; Escherichia coil; Salmonella spp.